Crop rotation suppresses soil-borne Fusarium wilt of banana and alters microbial communities. Issue 4 (21st March 2022) - Fan, Pingshan; Lai, Chaoyuan; Yang, Jinming; Hong, Shan; Yang, Yue; Wang, Qing; Wang, Beibei; Zhang, Rongping; Jia, Zhongjun; Zhao, Yan; Ruan, Yunze
ABSTRACT: Soil-borne Fusarium wilt disease causes damage to certain crops, but crop rotation may be an effective management strategy for this pest. Soil microbes may play an important role in this strategy, but the response of the soil microbial community to crop rotation is unclear. In a field experiment, we used high-throughput sequencing to study the effects of banana rotation with one of four other crops (pepper, sugarcane, wax gourd and pumpkin) or continuous cultivation of banana as a single crop on soil microbial community. Compared with monocropping, all crop rotation strategies led to a decrease in the incidence of Fusarium wilt of banana, while an increase in banana yields. The main bacterial phyla were Proteobacteria (24.96%), Acidobacteria (21.25%), Gemmatimonadetes (12.98%), and the fungal phyla was Ascomycota (72.54%), across the soil. These four crop rotation treatments also increased bacterial richness and the relative abundance of Acidobacteria, Gemmatimonadetes, Firmicutes, and Actinobacteria, while reducing the relative abundance of Proteobacteria, Chloroflexi, Parcubacteria, Cyanobacteria and Fusarium . Redundancy analysis showed that soil pH, organic matter and available phosphorus were the main factors affecting the composition of bacterial and fungal communities. Overall, we show that crop rotation can inhibit banana wilt and change soil microbial community composition.